Reaching and Teaching Students in Poverty: Strategies for Erasing the Opportunity Gap - Hernandez Goff, Maria (Educational (Re)naissance, 2020)
The second edition of Reaching and Teaching Students in Poverty: Strategies for Erasing the Opportunity Gap aims to move educators from a deficit view of students experiencing poverty to a structural view by examining the structural inequalities in the United States. This book encourages educators to develop equity literacy and provides twelve principles of equity literacy, supported by historical data and current research, to guide readers in this process. The book also offers actionable strategies to implement at the classroom, school, and district level.